2021
DOI: 10.3390/ijerph182413240
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Online COVID-19 Information Acquisition among Persons with Type 2 Diabetes and Varying eHealth Literacy

Abstract: During the COVID-19 pandemic, the Internet has been a major source of information for people to keep updated with news and guidelines. However, concerns have been raised about the ‘infodemic’, which includes the overabundance of online information and the spread of misleading information. Adequate eHealth literacy skills among world citizens have therefore been emphasized as vital during the pandemic. Persons with type 2 diabetes have been at increased risk of severe outcomes of COVID-19 disease. This study ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
(47 reference statements)
1
3
0
2
Order By: Relevance
“…Some participants in the study presented sleep disturbances, which, in many cases, were linked directly to COVID-19-related news. Concurring with our findings, a previous study reported that being exposed to information overload about COVID-19 can have a negative impact on the psychological health of T2DM participants [ 51 ]. Increases in time spent following news about COVID-19 predict declines in mental health and well-being in adults [ 37 ], whereas good sleep habits play an important role in the maintenance and restoration of good heath [ 52 ].…”
Section: Discussionsupporting
confidence: 89%
“…Some participants in the study presented sleep disturbances, which, in many cases, were linked directly to COVID-19-related news. Concurring with our findings, a previous study reported that being exposed to information overload about COVID-19 can have a negative impact on the psychological health of T2DM participants [ 51 ]. Increases in time spent following news about COVID-19 predict declines in mental health and well-being in adults [ 37 ], whereas good sleep habits play an important role in the maintenance and restoration of good heath [ 52 ].…”
Section: Discussionsupporting
confidence: 89%
“…27 No mesmo sentido, diferentes estudos que avaliaram as discussões sobre diabetes em redes e fóruns online mostraram que apesar do crescimento considerável de postagens durante a pandemia da COVID-19 e suas medidas de isolamento e distanciamento social, o conteúdo apresenta, na maioria das vezes, limitações capazes de impactar na prevenção e controle da doença. [34][35][36] Esses eventos estiveram associados principalmente à sobrecarga de informações, em geral conflitantes que repercutiram de forma direta nos comportamentos e estilo de vida dos pacientes, assim como no reconhecimento do risco e da gravidade que essa condição de saúde apresenta. 34,36 Desse modo, considera-se que as Novas Tecnologias de Informação e Comunicação (NTICs) podem desempenhar um papel fundamental no acesso e disseminação da informação e, consequentemente, para o empoderamento individual e coletivo.…”
Section: Discussionunclassified
“…[34][35][36] Esses eventos estiveram associados principalmente à sobrecarga de informações, em geral conflitantes que repercutiram de forma direta nos comportamentos e estilo de vida dos pacientes, assim como no reconhecimento do risco e da gravidade que essa condição de saúde apresenta. 34,36 Desse modo, considera-se que as Novas Tecnologias de Informação e Comunicação (NTICs) podem desempenhar um papel fundamental no acesso e disseminação da informação e, consequentemente, para o empoderamento individual e coletivo. 41 No campo da saúde, o empoderamento encontra-se estreitamente relacionado à informação.…”
Section: Discussionunclassified
“…Ladner et al (2022) showed that diabetes telenursing has more potential in rural areas. Studies have shown that (Christensen et al, 2022;Crowley et al, 2022;Iversen et al, 2020;Sjöström et al, 2021;Zhang et al, 2022) telenursing for diabetes can improve blood sugar control (Goh et al, 2021), induce behavioural changes, reduce hospitalization and prevent complications, thereby improving at-home diabetic self-management (María Gómez et al, 2022).The implementation of self-management behaviours requires access to disease-related social support resources, including but not limited to family, friends, medical professionals and reliable information sources (Glasgow et al, 2000). In reality, telenursing is the telematics-based remote implementation of in-person care services (Al-Badri et al, 2022), which by its very nature still depends on actual nursing resources (Anderson et al, 2022).…”
Section: Introductionmentioning
confidence: 99%